2020
DOI: 10.1177/1559325819901239
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 may Act as a Potential Mediator Between Inflammation and Abnormal Bone Formation in Ankylosing Spondylitis Based on TNF-α Concentration-Dependent Manner Through the JAK2/STAT3 Pathway

Abstract: Objective: To explore the role of microRNA (miR-21) in new bone formation in ankylosing spondylitis (AS) as mediated by different concentration of tumor necrosis factor-α (TNF-α). Methods: Fibroblasts isolated from the hips of patients with AS were induced to osteogenesis. These cells were then stimulated with varying concentrations of TNF-α. MicroRNA-21 expressions were evaluated using reverse transcription–polymerase chain reaction (RT-PCR) and osteogenesis was detected via Alizarin Red S (ARS) staining and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The possible reasons might be that: (a) elevated lnc-NEAT1 and decreased miR-21 and miR-125a could promote inflammatory cytokines and immune response, which consequently resulted in elevated inflammation in RA patients 7,19,20,23 ; and (b) increased lnc-NEAT1 and declined miR-21 and miR-125a might inhibit new bone formation and accelerate bone degradation through regulating several signaling pathways (such as Janus kinase 2/signal transducer, activator of transcription-3, and E26 transformation-specific-1 pathways), which could lead to high disease activity in RA patients. [24][25][26] Therefore, elevated lnc-NEAT1 but declined miR-21 and miR-125a were correlated with inflammation and disease activity in RA.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons might be that: (a) elevated lnc-NEAT1 and decreased miR-21 and miR-125a could promote inflammatory cytokines and immune response, which consequently resulted in elevated inflammation in RA patients 7,19,20,23 ; and (b) increased lnc-NEAT1 and declined miR-21 and miR-125a might inhibit new bone formation and accelerate bone degradation through regulating several signaling pathways (such as Janus kinase 2/signal transducer, activator of transcription-3, and E26 transformation-specific-1 pathways), which could lead to high disease activity in RA patients. [24][25][26] Therefore, elevated lnc-NEAT1 but declined miR-21 and miR-125a were correlated with inflammation and disease activity in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Balzano et al hypothesized that low expression of miR-21-5p was a result of corticosteroids that inhibit NF- κ B [ 94 ]. Further analyses revealed that miR-21 may be implicated in several signalling pathways such as the IL-34/STAT3/miR-21 pathway, essential for synovial fibroblast survival in RA [ 95 ], as well as a mediator between inflammation and bone formation through the JAK2/STAT3 pathway in AS [ 96 ]. Additionally, miR-21 plays a role in mediation of RANKL-induced osteoclastogenesis and downregulation of programmed cell death 4 (PDCD4) protein levels [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…RevertAid™ H Minus First Strand cDNA Synthesis Kit (Fermentas) was used to prepare the mRNA reverse transcription system to synthesize cDNA by reverse transcription. The primer sequences of miRNA-21, miRNA-145, miRNA-155, and miRNA-199b-5p are as previously documented ( 17-20 ).…”
Section: Methodsmentioning
confidence: 99%